Respuesta :
Answer:
Sec²x
Step-by-step explanation:
Check attachment
I hope this was helpful, Please mark as brainliest.
![Ver imagen oladipupog80](https://us-static.z-dn.net/files/d90/d919f1a9c00520452e4bf9bd4e2c9876.jpg)
Answer:
dy/dx = 1/cos²x or dy/dx = 1 + tan²x or dy/dx == sec²x
Step-by-step explanation:
hello :
note :
1) dy/dx= cosx if y = sinx
2) dy/dx= - sinx if y = cosx
3) cos²x +sin²x = 1 ...(**)
4) tanx = sinx/cosx
5) d(f/g) = (g×df-f×dg)/g²...(*)
now : let : y = tanx and f(x)= sinx g(x) = cosx
use (*) : dy/dx = (cosx(cosx) - sinx(-sinx)) / cos²x = (cos²x +sin²x)/ cos²x
use (**) : dy/dx = 1/cos²x or dy/dx = (1/cosx)² = sec²x
or : dy/dx =(cos²x +sin²x)/ cos²x = cos²x/cos²x + sin²x/ cos²x = 1+sin²x/ cos²x
dy/dx = 1 + (sinx/cosx)²
dy/dx = 1 + tan²x